A Bifunctional 2D Interlayered β‐Cu2V2O7/Zn2V2O6 (CZVO) Heterojunction for Solar‐Driven Nonsacrificial Dye Degradation and Water Oxidation. Issue 7 (6th May 2021) - Ashraf, Muhammad; Khan, Ibrahim; Baig, Nadeem; Hendi, Abdulmajeed H.; Ehsan, Muhammad Fahad; Sarfraz, Nafeesa
Abstract : Investigating novel materials with controlled morphology for solar‐driven conversions is the foremost research emphasis in applied sciences. In continuation of those efforts, we report the unique synthesis of a novel trimetallic β‐Cu2 V2 O7 /Zn2 V2 O6 (CZVO) hybrid with controlled morphology. The trimetallic CZVO demonstrates a bifunctional, non‐sacrificial photoresponse in the cases of 1) photocatalytic degradation using methylene blue (MB) as a model dye; and 2) photoelectrochemical (PEC) water oxidation. The X‐ray photoelectron spectroscopy (XPS) analysis of CZVO confirmed Type‐(I) heterojunction formation between β‐Cu2 V2 O7 (CVO) and Zn2 V2 O6 (ZVO). After visible light exposure (65 min), CZVO‐opt (1 wt% CVO: 5 wt% ZVO) demonstrated the highest photodegradation, while the CZVO‐opt photoanode delivered the highest photocurrent density ( I ph ) of 1.78 mA cm −2 at 1.23 VRHE, almost 3.11 and 1.55 times more than CVO ( I ph = 0.57 mA cm −2 ) and ZVO ( I ph = 1.15 mA cm −2 ) photoanodes, respectively. The CZVO‐opt photoanode harvested the most solar energy in terms of incident photon to current conversion efficiency (IPCE320 nm = 37.93%). The significant improvement in the CZVO‐opt performance can be attributed to the firm contact and uniform distribution of ZVO NPs over CVO interlayered nanosheets, which leads to adequate solar absorption and facile charge transport through a Type‐(I) heterojunction with suppresses charge recombination. Abstract : The novel trimetallic β‐Cu2 V2 O7 /Zn2 V2 O6 (CZVO‐opt) heterojunction shows a bifunctional and nonsacrificial photocatalytic response for the photodegradation of methylene blue dye and enhanced photoelectrochemical (PEC) water oxidation under visible light.